Early Predictors of Enteral Autonomy in Pediatric Intestinal Failure Resulting From Short Bowel Syndrome: Development of a Disease Severity Scoring Tool. Issue 8 (28th August 2019) - Belza, Christina; Fitzgerald, Kevin; de Silva, Nicole; Avitzur, Yaron; Wales, Paul W.
Abstract: Introduction: Patients with short bowel syndrome (SBS) are dependent on parenteral nutrition (PN) while their bowel attempts to compensate. Our objective was to create an SBS disease severity score to predict the probability of achieving enteral autonomy (EA). Methods: A retrospective cohort study of children with SBS managed by our Intestinal Rehabilitation Program was completed. Data abstracted included demographic, bowel anatomy, and outcome variables including conjugated bilirubin (CB) and enteral nutrition (EN) tolerated 6 months postoperatively. Univariate analysis and Cox proportional hazards (CPH) model were performed. A score was created based on weighting of coefficients. An α‐value of < 0.05 was considered significant. Results: One hundred thirty‐nine patients were analyzed (61% males). Ninety‐five (68%) achieved EA. Patients possessing >50% residual small bowel (hazard ratio [HR] 2.68 [95% confidence interval CI 1.60‐4.49], P < 0.001), ileocecal valve intact (HR 0.61 [95% CI 0.37‐1.01], P < 0.055), and >50% enteral tolerance at 6 months (HR 5.70 [95% CI 2.77‐11.74] P < 0.001) were positively associated with EA. CB >34 µmol/L (2 mg/dL) was negatively associated with EA (HR 0.42 [95% CI0.27‐0.66], P < 0.001). A severity score was created by weighting CPH parameter estimates (small bowel length >50%, ileocecal valve intact, CB <34 µmol/L, and EN >50% for a maximum score of 8), and disease severity strata were developed (severe [25.7% EA], moderate [52.9% EA], and mild [97.1% EA]). Conclusion: We propose a pediatric SBS disease severity score that predicts probability of EA. The score allows prognostication of individual patients and could assist research by adjusting outcome reporting or stratifying recruitment.